Dietary Supplementation With Fine-Grinding Wheat Bran Improves Lipid Metabolism and Inflammatory Response via Modulating the Gut Microbiota Structure in Pregnant Sow - Wang, Zijie; Chen, Yifan; Wang, Wenhui; Huang, Caiyun; Hu, Yongfei; Johnston, Lee; Wang, Fenglai (Frontiers in Microbiology, 2022)
This study investigated effects of fine-grinding wheat bran on pregnant sow body condition, lipid metabolism, inflammatory response, and gut microbiota. In this study, wheat bran was crushed into three particle sizes. And a total of sixty Landrace × Yorkshire second parity sows were allotted to two groups: CWB (a diet contained coarse wheat bran with particle size of 605 μm) and FWB (a diet contained fine wheat bran with particle size of 438 μm). Fine-grinding wheat bran had higher soluble dietary fiber concentration, swelling capacity, water holding capacity, and fermentability than coarse wheat bran (p < 0.05). Pregnant sows fed FWB throughout pregnancy had lower body weight and fat deposition than sows fed CWB. And the piglet body weight at birth of FWB group was remarkably increased. Serum concentrations of lipids (triglycerides, total cholesterol, and free fatty acid), interleukin 6, leptin, and resistin were decreased on d 90 of pregnancy by fine wheat bran supplementation. Feeding FWB significantly decreased abundance of Firmicutes and dramatically increased the abundance of Bacteroidetes at phylum level. At genus level, the abundance of Terrisporobacter was decreased in FWB feeding sows, but the abundance of Parabacteroides was increased. Fecal total short-chain fatty acids, propionate, and butyrate contents were markedly increased in FWB group. The results suggested that the physicochemical properties of finely-ground wheat bran had been improved. Dietary supplementation with fine wheat bran changed gut microbiota structure and enhanced short-chain fatty acids level, which improves maternal body condition, metabolic and inflammatory status, and reproductive performance in sows.